Combined application of BNLF2b antibody with VCA-IgA, Rta-IgG, and Zta-IgA in nasopharyngeal carcinoma screening in the Guangxi region - Ruilan Lin; Ru Qin; Yunlong Zhang; Yao Guan; Boheng Wu; Shangyang Li; Shenhong Qu; Yulin Yuan (PLoS ONE, 2025)
Background This study aims to assess the diagnostic value of the Epstein-Barr virus (EBV) BNLF2b antibody(P85-Ab), alone or in combination with VCA-IgA, Rta-IgG, and Zta-IgA antibodies, in the context of nasopharyngeal carcinoma (NPC). Methods The study included 100 NPC patients and 100 healthy controls. Chemiluminescent microparticle immunoassay was utilized to measure P85-Ab levels in the serum samples of both NPC patients and healthy controls. Additionally, the ELISA method was employed to detect serum levels of VCA-IgA, Rta-IgG, and Zta-IgA antibodies. The study analyzed the roles of serum P85-Ab in conjunction with VCA-IgA, Rta-IgG, and Zta-IgA antibodies in the diagnosis of NPC. Results Serum levels of P85-Ab, VCA-IgA, Rta-IgG, and Zta-IgA antibodies in NPC patients were significantly higher than those in the normal control group (P < 0.05). The area under the receiver operating characteristic curve (AUC) for individual diagnosis of NPC using serum P85-Ab, VCA-IgA, Rta-IgG, and Zta-IgA antibodies were 0.964, 0.916, 0.838, and 0.840, respectively. The AUC for the combined detection of the four markers in diagnosing NPC was 0.996, indicating the optimal diagnostic value of the combined detection. Conclusion The combined detection of P85-Ab with VCA-IgA, Rta-IgG, and Zta-IgA antibodies demonstrates high diagnostic value for nasopharyngeal carcinoma. Serum P85-Ab may serve as a potential marker for the diagnosis of NPC.